Geographic distribution and parturition of mabuya arajara Rebouças-Spieker, 1981 (Squamata, sauria, scincidae) from Ceará, northeastern Brazil - Roberto, Igor Joventino (2010)
Mabuya arajara Rebouças-Spieker, 1981 has been considered an endemic species from the southern of state of Ceará, restricted to the Deciduous Dry Forests in the slopes of Plateau of Araripe (Chapada do Araripe). Here, we present an updated distributional map for the species and demonstrate that its range is not restricted as formerly believed. In addition, we had an opportunity to observe a gravid female and we describe aspects regarding parturition and number of offspring for the species.